2012
DOI: 10.1063/1.3671745
|View full text |Cite
|
Sign up to set email alerts
|

Electron density measurement of cesium seeded negative ion source by surface wave probe

Abstract: Electron density measurements of a large-scaled negative ion source were carried out with a surface wave probe. By comparison of the electron densities determined with the surface wave probe and a Langmuir probe, it was confirmed that the surface wave probe is highly available for diagnostic of the electron density in H(-) ion sources. In addition, it was found that the ratio of the electron density to the H(-) ion density dramatically decreases with increase of a bias voltage and the H(-) ions become dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…3 In this study, the electron density measurement was carried out by the SWP at various bias voltages in the pure-volume and Cs-seeded plasmas. We will discuss effects of the grid bias on electrons in the different negative ion production processes.…”
Section: Introductionmentioning
confidence: 99%
“…3 In this study, the electron density measurement was carried out by the SWP at various bias voltages in the pure-volume and Cs-seeded plasmas. We will discuss effects of the grid bias on electrons in the different negative ion production processes.…”
Section: Introductionmentioning
confidence: 99%
“…The latter also affects the electron temperature. This is predicted by numerical simulations [17,21] and demonstrated experimentally in other existing negative ion sources [10,27]. However, this is the first time that the effect of these parameters in a large source as SPIDER is studied.…”
Section: Plasma In the Expansion Regionmentioning
confidence: 61%
“…The electron density results obtained with the surface wave probe for Cs seeded conditions were one-to two-order of magnitude lower than those without Cs [83]. The surface wave probe results have also shown that the dependence of electron density upon the plasma electrode bias resembles the dependence of the electron drain current upon the plasma electrode bias [84]. Namely, the plasma electrons are the cause of coextracted electron current.…”
Section: Plasma Parametersmentioning
confidence: 99%